Pengaruh Harga, Promosi, dan Switching Barrier terhadap Loyalitas Pelanggan dengan Kepuasan sebagai Variabel Intervening: Studi pada Pelanggan Kartu Telkomsel dikalangan Gen Z Kec. Palu Barat - Nurul Khairia Lim Fatimah; Nur Wanita; Nurfitiriani Nurfitiriani (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to examine in depth the influence of price, promotion, and switching barriers on customer loyalty of Telkomsel prepaid cards, with customer satisfaction as an intervening variable in Generation Z in West Palu District. This study is motivated by the intense competition in the telecommunications industry and the importance of maintaining customer loyalty amidst the increasing number of service options. Data were collected from 100 respondents who are active Telkomsel prepaid card users through questionnaires. Data analysis was conducted using the Structural Equation Modeling-Partial Least Squares (SEM-PLS) approach using SmartPLS software version 4.0. The results show that the price variable has a significant direct effect on customer loyalty, but does not show a significant effect on customer satisfaction. Conversely, promotion has a significant effect on satisfaction, but does not directly affect customer loyalty significantly. Switching barriers are shown to have a significant effect on both satisfaction and loyalty, indicating that the higher the switching barriers, the more likely customers will remain loyal. In addition, customer satisfaction also significantly affects loyalty. Another important finding is that of the several indirect influences tested, only the path from promotion through satisfaction to loyalty was statistically significant. Therefore, this study suggests the importance of targeted promotional strategies and strengthening switching barriers as effective measures in retaining young customers who are prone to switching services. Furthermore, this study emphasizes that customer loyalty is not solely determined by competitive pricing factors, but is more complex and influenced by customers' emotional and psychological experiences, such as satisfaction with the service and perceptions of the ease or difficulty of switching to another service provider.